Anticlone Gaussian attack for continuous variable EPR correlations - Messikh Azeddine, Azeddine; Bouketir, Ahmed; Umarov, Bakhram A.; Wahiddin, Mohamed Ridza (sciverse, 2007)
We investigate the security of a model based on continuous variable QKD with Einstein-Podolsky-Rosen correlations against Gaussian clone-anticlone attacks. We find that the eavesdropper distils more information using the individual Gaussian anticlone attack than the optimal Gaussian cloner. However, a secure key can still be generated for the transmission coefficient of the quantum channel bigger than 0.5. Thus, the model is secure for clone-anticlone attacks.